Indications for accurate and appropriate use of personal protective equipment for healthcare professionals: A systematic review - Peccin, Maria Stella (2022)
BACKGROUND: The speed of the spread of coronavirus disease 2019 (COVID-19) has put enormous pressure on hospitals and other healthcare facilities. This, together with blockages in several countries, has hindered the availability and accessibility of the necessary personal protective equipment (PPE). OBJECTIVE: To identify, systematically evaluate and summarize the available scientific evidence on the efficacy, safety, safe use and reuse of PPE for healthcare professionals, for preventing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. DESIGN AND SETTING: Systematic review of studies analyzing products for disinfecting and enabling reuse of PPE for coronavirus within the evidence-based health program of a federal university in São Paulo (SP), Brazil. METHODS: A systematic search of the relevant literature was conducted in the PubMed, EMBASE, Cochrane Library, CINAHL, SCOPUS, Web of Science and LILACS databases, for articles published up to November 30, 2020. RESULTS: Ten studies were selected. These analyzed the use of N95, surgical and cotton masks, face shields, flexible enclosures with plastic covers or polycarbonate intubation boxes and plastic curtains; and also PPE disinfection using several substances. CONCLUSION: Combined use of a face shield with a N95 mask proved to be superior to other associations for protecting healthcare workers. Some products are useful for disinfecting PPE, such as 70% ethanol, 0.1% sodium hypochlorite and a mixture of quaternary ammonium and H2O2, and hydrogen peroxide. Ultraviolet light and dry heat at 70 °C can be used to decontaminate N95 masks. REGISTRATION NUMBER: DOI: 10.17605/OSF.IO/4V5FD at the OPENSCIENCE Framework.